Mainstreaming of genomic medicine in gastroenterology, present and future: a nationwide survey of UK gastroenterology trainees - Gregory Malcolm Sebepos-Rogers; Hilary Burton (BMJ Open)
Objective Genomics and personalised medicine are increasingly relevant for patients with gastroenterological conditions. We aim to capture the current state of genomics training in gastroenterology to review current understanding, clinical experience and long-term educational needs of UK trainees.Design and setting A web-based nationwide survey of all UK gastroenterology specialty trainees was conducted in 2017.Results 100 trainees (14% of UK gastroenterology trainees) completed this survey. Only 9% and 16% of respondents believe that their local training programme adequately prepares them for the future clinical practice using genomic medicine and personalised medicine, respectively. Barriers identified include the need for greater trainee education (95%), inadequate clinical guidance to base interventions on the results of genomic testing (53%), concerns over misinterpretation by patients (43%) and overuse/misuse of testing by clinicians (34%).Survey respondents felt prepared to perform HFE genotyping (98%), assess TPMT status (97%) and interpret HLA subtyping for suspected coeliac disease (85%). However, only a minority felt prepared to perform the following investigations: polyposis screening (34%), hereditary pancreatitis screening (30%), testing for Lynch yndrome (33%) and KRAS testing for colorectal cancer (20%).Most respondents would support holding dedicated training days on genomic medicine (83%), formal training provisions for the mainstreaming of genomic testing (64%), an update to the UK gastroenterology specialty training curriculum and examinations (57%) and better-defined referral pathways for local genomic services (91%).Conclusion Most gastroenterology trainees in this survey feel ill equipped to practise genomic and personalised medicine as consultants. We propose specific revisions to the UK gastroenterology specialty curriculum that addresses trainees needs.